PENYALURAN ZAKAT PROFESI DI LAZISMU SURAKARTA - Syahril Sidiq; Yayuli Yayuli (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
The large number of poverty in Indonesia, makes our attention wake up to immediately help and eradicate poverty slowly. Lazismu Surakarta as the manager of zakat funds, is expected to be able to answer public concerns about the many poor people who are easily found in Surakarta. The focus of this research is the distribution of professional zakat in Lazismu Surakarta in the period 2020. The type of this research is field research and is descriptive in nature and this research approach uses qualitative research methods. The results of this study indicate that Lazismu Surakarta in the management of zakat funds is in accordance with Islamic law. The programs given to mustahik are adapted to their daily needs. For the type of assistance provided in the form of business capital and production equipment, of course it has gone through careful screening and selection. Professional zakat, which has just been enlivened by Lazismu Surakarta, has contributed to Lazismu Surakarta programs, although it is only 6% of the total other zakat funds. That's been quite good in its development in the 2019-2020 period.